2000
DOI: 10.2166/nh.2000.0007
|View full text |Cite
|
Sign up to set email alerts
|

Snow Wetness Influence on Impulse Radar Snow Surveys Theoretical and Laboratory Study

Abstract: The snow-water equivalent of late-winter snowpack is of utmost importance for hydropower production in areas where a large proportion of the reservoir water emanates from snowmelt. Impulse radar can be used to estimate the snow-water equivalent of the snowpack and thus the expected snowmelt discharge. Impulse radar is now in operational use in some Scandinavian basins. With radar technology the radar wave propagation time in the snowpack is converted into snow-water equivalent with help of a parameter usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
0
21
0
3
Order By: Relevance
“…On the other hand, the LWC directly upon upGPR and GPS can easily vary due to rapid melting processes within the ripe snowpack (end of June 2013 and beginning of June 2014). Moreover, the formulas applied for the complex permittivity are only valid up to a LWC of approximately 8% [ Lundberg and Thunehed , ; Mitterer et al , ]. However, these deviations were only observed at the very end of the snow‐covered season; overall, the agreement between both systems was very good.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the LWC directly upon upGPR and GPS can easily vary due to rapid melting processes within the ripe snowpack (end of June 2013 and beginning of June 2014). Moreover, the formulas applied for the complex permittivity are only valid up to a LWC of approximately 8% [ Lundberg and Thunehed , ; Mitterer et al , ]. However, these deviations were only observed at the very end of the snow‐covered season; overall, the agreement between both systems was very good.…”
Section: Discussionmentioning
confidence: 99%
“…However, they reported that quantitative interpretation is challenging due to, for example, air pockets that easily form around the sensors. Nondestructive measurements of wet-snow or even LWC alongside with the determination of further snow cover properties were obtained with different radar systems (e.g., Bradford et al, 2009;Heilig et al, 2015;Lundberg & Thunehed, 2000;Mitterer et al, 2011;Schmid et al, 2014) but are rather expensive for operational application.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Lundberg et al () assumed density to be linearly dependent on snow depth. However, when liquid water is present in the snowpack, data analysis methods become more complex and snow water equivalent estimations are typically more uncertain (Lundberg & Thunehed, ). Bradford and Harper () determined the liquid water content by using the frequency shift method to estimate the complex electrical permittivity and by using the common midpoint (CMP) method to estimate the real part of the electrical permittivity.…”
Section: Introductionmentioning
confidence: 99%